A new species of Freycinetia Gaudich. (Pandanaceae; Freycinetoideae) from Tidore Island, Moluccas, Indonesia. - Ary Prihardhyanto Keim (REINWARDTIA, 2013)
Freycinetia tidorensis A.P. Keim is newly described from Tidore Island, Moluccas. This  new species is morphologically similar to F.  devriesei Solms  but differs in the number of stigmatic remains.  In F. devriesei the number is 3 to 6, never less than 3; whereas in Freycinetia tidorensis 1 to 2, never more than 2.